Mammals Make Use of Cashew Plantations in a Mixed Forest–Cashew Landscape - Rege, Anushka; Punjabi, Girish Arjun; Jathanna, Devcharan; Kumar, Ajith (Frontiers in Environmental Science, 2020)
Heterogeneous landscapes harbouring mosaics of natural habitat and agriculture are increasingly gaining conservation focus in the tropics. While research on cash crops such as coffee, rubber, and oil palm has led to an understanding of their role as supplementary habitats, such has remained limited in cashew plantations despite it being a cash crop of global significance. We conducted a study to understand the occurrence of terrestrial mammal species in a mixed forest-cashew landscape in the northern Western Ghats, India. During January to April 2016, we used trail cameras to sample a total area of 25 km2 divided into 100 grid cells of 0.25 km2 each. We deployed six trail cameras for a 24-hour period in each grid cell and obtained photo-captures of eleven species in forests, of which nine were detected in cashew plantations, but most species showed low capture rates. For three of these species - Indian crested porcupine, sambar, and wild pig, we modelled habitat-use as a function of site-specific attributes. Wild pig showed higher probability of use of cashew than forest, while porcupine and sambar did not show any pronounced differences between the two land-uses. The probability of habitat-use by sambar and porcupine was positively influenced by undergrowth but not for the wild pig. Wild pig habitat-use was positively related to increased proximity of human settlements and increasing distance to forests but the pattern was unreliable for sambar and porcupine. Our preliminary study demonstrates that a subset of terrestrial mammals in the forest make use of cashew plantations and highlights the need for further research in forest-cashew landscapes to assess conservation opportunities.